The drivers of oil prices: The usefulness and limitations of non-structural models, supply-demand frameworks, and informal approaches - Bassam Fattouh (EIB Papers, 2007)
This paper discusses three main approaches for analysing oil prices: non-structural models, the supplydemand framework, and the informal approach. Each approach emphasises a certain set of drivers of oil prices. While non-structural models rest on the theory of exhaustible resources, the supply-demand framework uses behavioural equations that link oil demand and supply to its various determinants. The informal approach focuses on the specifics of oil market history in explaining oil prices. Although all approaches provide useful insights on how the world oil market functions, they suffer from major limitations especially when used for long-term projections. Thus, pushing hard for policies based on such projections defeats the purpose of such models and may result in misguided policies.
Keywords: 330; Ölpreis; Mineralölmarkt; Ressourcenökonomik; Welt; OPEC-Staaten